Assessment of genetic diversity in rice genotypes for salinity tolerance using Saltol markers of Chromosome 1 - Krishnamurthy, S. L.; Sharma, S. K.; Kumar, V.; Tiwari, S.; Batra, V.; Singh, N.K. (The Indian Journal of Genetics and Plant Breeding, 2017)
The present study was conducted to assess the genetic diversity using Saltol markers among 57 rice genotypes. The material was screened in hydroponics using salinized (EC 10 dS/m) nutrient solution. Based on seedling stage salinity tolerance, the genotypes were grouped as highly tolerant, tolerant, moderately tolerant, sensitive and highly sensitive. Eight out of 21 SSR markers used were polymorphic. The PIC values ranged from 0.52 to 0.82 with an average of 0.74. The genotypes namely, FL 478, Pokkali,Trichi 1 and Trichi 2 were grouped in cluster I and were highly salinity tolerant. Clusters II, III, IV and VIII had single genotype each, which showed moderate tolerance to salinity stress. The genotypes in cluster VII exhibited moderate to high tolerance, while cluster VI had genotypes with mixed response to salinity. Salt tolerance in IR 64 could be improved by inter-crossing with salt-tolerant genotypes. Information generated from the present study would be useful in selection of parents and for markeraided salinity breeding programs in rice.